Upaya Orang Tua dalam Meningkatkan Motivasi Anak Usia 7 Tahun Membaca Al-Qur'an - Ashoumi, Hilyah; Sholikhah, Umi Maratus (Universitas KH. A. Wahab Hasbullah, 2024)
This study examines the efforts of parents in motivating 7-year-old children to read the Qur'an at TPQ Babussa'adah Murukan Mojoagung Jombang and the obstacles faced. The research method used is qualitative and descriptive. Data were obtained through interviews, observations, and documentation studies with parents of students and related literature. Data analysis includes data reduction, presentation, findings, and verification. Through triangulation and involvement, data accuracy was checked. This study found that parents can motivate 7-year-old children to read the Qur'an by implementing it at home, providing motivation, scheduling the habit of reading the Qur'an after the Maghrib prayer, giving gifts, and involving them in religious activities in the community. Research suggestions are to provide counseling, create a good environment for memorizing the Qur'an, limit cellphone use, and be consistent in providing consequences to overcome children's lethargy. YouTube, TikTok, and television that are not time-dependent hinder reading the Qur'an. Inviting friends to play during study time is the next step.